If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3b + -2(b + 4) = 8(b + -1) Reorder the terms: 3b + -2(4 + b) = 8(b + -1) 3b + (4 * -2 + b * -2) = 8(b + -1) 3b + (-8 + -2b) = 8(b + -1) Reorder the terms: -8 + 3b + -2b = 8(b + -1) Combine like terms: 3b + -2b = 1b -8 + 1b = 8(b + -1) Reorder the terms: -8 + 1b = 8(-1 + b) -8 + 1b = (-1 * 8 + b * 8) -8 + 1b = (-8 + 8b) Add '8' to each side of the equation. -8 + 8 + 1b = -8 + 8 + 8b Combine like terms: -8 + 8 = 0 0 + 1b = -8 + 8 + 8b 1b = -8 + 8 + 8b Combine like terms: -8 + 8 = 0 1b = 0 + 8b 1b = 8b Solving 1b = 8b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-8b' to each side of the equation. 1b + -8b = 8b + -8b Combine like terms: 1b + -8b = -7b -7b = 8b + -8b Combine like terms: 8b + -8b = 0 -7b = 0 Divide each side by '-7'. b = 0 Simplifying b = 0
| x-4+6x-8x=3 | | 3(4X-3)=-81 | | 8(2x+3)-5=16x+19 | | -7(3v+6)=-7v+32 | | 3(x-7)=23-(3x+2) | | 6(4X+4)=24 | | -63+105= | | 18-m=9+3 | | -37=3w+11-7w | | -9*7= | | 4(5-n)=-16 | | 7y-12=4y+6 | | y=100+.80y+100 | | 3-(x+7)=23-(3x+2) | | 7(x+3)=4x | | -2.3x=34.04 | | 7(x+3)=4c | | 3(x+4)=35 | | -8x+4x+19-12x= | | 7(x+3)=4b | | 0+41=51 | | 3n-9=-9 | | .8x+9=.6x-6 | | 7x-10=-21x-4 | | (N-13)+4=5 | | 30n-40=29 | | 9-2u=15-4u | | 14n=29 | | 7h-5=4h+22 | | -51x=4.41 | | 24x^2-24x-18=0 | | .375a-4=.25 |